Extraction of essential oil from kaffir lime (Citrus hystrix) leaves using microwave-assisted extraction / Siti Nurfatihah Azmi, Muhammad Syafiq Hazwan Ruslan - Azmi, Siti Nurfatihah; Ruslan, Muhammad Syafiq Hazwan (Universiti Teknologi MARA Shah Alam, 2022)
Citrus hystrix DC or normally known as kaffir lime is a citrus species from the Rutaceae family with valuable properties that have attracted the interest of the public. Not only that but the leaves and fruits of the kaffir lime also have a diverse range of essential oils and are therefore used for essential oils extraction. The potential for the commercialisation of kaffir lime essential oil on a large scale in the industry remains a challenge due to the low yield of essential oils produced by conventional methods. In this study, microwave-assisted extraction (MAE) has been chosen as an excellent alternative for essential oil extraction to replace conventional industrial methods. The objectives of this study were to identify the optimum particle size, extraction time, and percentage of co-solvent used for obtaining high extraction oils yield and analyse the volatile compounds of extracted kaffir lime essential oils by using gas chromatography-mass spectrum (GC-MS) analysis. Throughout the extraction, the mass of the sample and power in the MAE process remains constant at 6.0 ± 0.003 g and 600 W, respectively. The mathematical models proposed for the study are the quadratic model for both extraction yield and mass of fatty acid recovered and the two-factor interaction for the mass of ester recovered. The optimum essential oil yield was determined as the particle size is 400 μm, extraction time of 14.95 min, and percentage of ethanol is 14.07% resulting in a yield of 23.54%. The GC-MS analysis resulted in the identification of almost 94 compounds for each of the samples. The identified major compounds from kaffir lime leaf oils were esters and followed by fatty acids.